Dynamic Supervision and Control of VOCs Emission From China’s Furniture Manufacturing Based on Big Data and IoT - Chen, Zi-Gui; Wu, Wei-Ping; Li, Jing; Zeng, Yu-Heng (Frontiers in Environmental Science, 2022)
How to effectively monitor and prevent VOCs in furniture manufacturing has become the key to solve the dilemma between furniture industry development and public health. Based on the combing of VOCs emission standards and prevention policies of China's furniture manufacturing, this paper explores the path of dynamic monitoring, intelligent prevention and control of VOCs embedded in furniture manufacturing with big data and IoT, and puts forward feasible VOCs control technologies in the whole process of China's furniture manufacturing, including source, process and end. The dynamic monitoring, intelligent prevention and control of VOCs in furniture manufacturing in this paper has important reference significance for the prevention and control of VOCs in other industries such as coal chemical industry, rubber products, engineering machinery, and coiled materials.